A Generation at Risk: The Impacts of Lebanon's Escalating Humanitarian Crisis on Children - Abouzeid, Marian; Halwani, Dana A.; Mokdad, Ali H.; Habib, Rima R. (Frontiers in Public Health, 2021)
Lebanon is in the midst of a rapidly escalating, unprecedented humanitarian crisis that is plunging the country deep into poverty and threatens population well-being, economic development, social welfare and national and regional stability. The dire situation is due to the compounding effects of the August 2020 Beirut blast, massive economic collapse and the COVID-19 pandemic, in a setting of longstanding entrenched political corruption and a dysfunctional, mismanaged crisis response by the state. This current emergency occurs on the background of a turbulent history and complex regional geopolitical context – including the Syrian refugee crisis, the ongoing influence of foreign actors and their local proxies, the United-States-imposed sanctions, endemic corruption, a culture of nepotism and entitlement among the political dynasties, dysfunctional power-sharing and deep-seated sectarian divides. With over half the population now living in poverty, a generation of children are among those at risk. This Perspective provides a brief overview of Lebanon's current complex humanitarian crisis, discusses the impacts of the evolving situation on youth and proposes a suite of recommendations to mitigate the effects.